Identifying the optimal monopolar electrocautery output power in pedicular internal thoracic artery harvesting: 20 or 40 watts? - Ata, Emin Can; Erkanlı Şentürk, Gözde; Saygı, Halil İbrahim; Ulukan, Mustafa Özer; Uğurlucan, Murat; Erkanlı, Korhan; Beyaz, Metin Onur; Yıldız, Erkan (NLM (Medline), 2022)
BACKGROUND: Monopolar electrocautery is an important tool for harvesting the pedicular internal thoracic artery (ITA) in cardiac surgery. The different power outputs of cautery may affect graft integrity and long-term patency. This study aimed to identify the optimal threshold of electrocautery power for ITA harvest. METHODS: This prospective study included 30 patients who underwent elective coronary artery bypass surgery at the Medipol Mega University Hospital. The ITA was harvested by monopolar electrocautery after a median sternotomy. The output of cautery was adjusted at 20 W in group A and 40 W in group B. Three to 4 cm of a distal ITA sample from each patient was examined under a light microscope by two independent pathologists. RESULTS: The ITA harvest time was longer in group A (21.2 ± 7.5 vs 10.3 ± 8.1 min, p < 0.001) than in group B. ITA free flow was similar in the two groups (43.6 ± 48.7 vs 51.7 ± 45.0 Ml/min, p = 0.762). Mild to moderate injury in the endothelial and sub-endothelial sample was more frequent in the low-cautery group (p = 0.0037). CONCLUSIONS: ITA endothelial integrity was found to be better preserved with 40W electrocautery. Moreover, 20W of monopolar electrocautery may not be safe in pedicular ITA harvesting.
Keywords: Coronary Artery Bypass; Electrocautery; Endothelial Injury; Internal Thoracic Artery